Association between intimate partner psychological violence and psychological distress among nurses: The role of personality traits and social support - Huang, Wentao; Zhang, Fan; Sun, Xibin; Yu, Qing; Huang, Jingxin; Su, Yunhui; Lan, Yutao (Frontiers in Psychology, 2023)
Aim This study proposes investigating the risk and protective factors of intimate partner (IP) psychological violence and psychological distress to better promote psychological wellbeing for nurses and health outcomes for patients. Design A cross-sectional study. Method This cross-sectional study was carried out chiefly in Guangdong, Hunan, and Shaanxi provinces, in the east, central, and west of the Chinese economic areas, respectively. It was conducted in October 2021 using convenience sampling. A total of 843 nurses were eligible for the final analysis. Single-factor linear regression models were used to identify potential factors associated with IP psychological violence and psychological distress. In addition, the structural equation model was used to explore the role of personality traits and social support in the association between IP psychological violence and psychological distress. Results The predictors for the score of IP psychological violence among nurses were participants' married status, contact frequency with a partner, perceived past-year psychological and physical violence experience, the alcohol consumption of partners, and personality traits and social support of partners. Moreover, the alcohol consumption of participants, the past-year experience of IP psychological violence, the score of psychological violence, personality traits, social support, and the personality traits of partners were associated factors affecting the psychological distress of nurses. In the structural model, the personality trait of partners had a direct pathway to psychological violence and social support. The results demonstrated that psychological violence significantly increased psychological distress. Conclusion Personality traits and social support are essential factors influencing the relationship between IP psychological violence and psychological distress. Impact The findings of this study emphasize the possibility and importance of identification and intervention for reducing IP psychological violence based on personality traits and social support.